Coronanomics: Strategi Revitalisasi UMKM Menggunakan Teknologi Digital di Tengah Pandemi Covid-19 - Yuwana, Siti Indah Purwaning (Fakultas Ekonomi, Universitas Ichsan Gorontalo, 2020)
The increasing spread of Covid-19 has had a tremendous impact on various sectors, especially in the health and economy sectors. MSMEs spread across Indonesia have a significant role in economic growth in Indonesia, and are also affected by the Covid-19 pandemic. Researchers saw the importance of implementing digital marketing and transactions in the sustainability of MSME businesses in Jember Regency during the Covid-19 pandemic. This research uses a qualitative approach, namely literature study and descriptive study using a sample of informants from MSME actors in Jember Regency. The results of this study prove that the application of digital marketing and transactions has a positive influence on the sustainability of MSMEs in Jember Regency while still paying attention to the rules of social distancing. So it is deemed necessary to be implemented in the midst of the Covid-19 Pandemic. In addition, Government support is needed in terms of accelerating the revitalization of digitalization in MSMEs, both in terms of policies and program alignments for MSMEs. Researchers at the end provide several alternative programs that can be run as a form of initiating national economic resilience through the revitalization of MSMEs.